Full-Length Transcriptome Analysis of the Pituitary of Pre-Matured and Artificially Matured Female Japanese Eel (Anguilla japonica) - Yu Gao; Jiangling Li; Zhenguang Feng; Mingxi Huang; Wen Li; Ruihan Xu; Ruoxue Chen; Yu Ban; Jingjie Liang; Yan Huang; Yangjie Xie; Jianchun Chen; et al. (Journal of Ocean University of China, 2026)

Molecular characterization of the medaka (Oryzias latipes) Hsp90ab1 - Ronggui Dai; Mengyang Wang; Lei Chen; Mingxi Huang; Ju Deng; Yan Huang; Tiansheng Chen (Fish & Shellfish Immunology, 2025)

Efficient hydrogen generation from ammonia borane hydrolysis over alkynyl-polyvinyl-alcohols decorated silica nanosphere supported ruthenium nanocatalyst - Xinxin Zhang; Yu Zhang; Kangzhou Wang; Deshun Huang; Kuan-Guan Liu; Xinhua Gao; Jianli Zhang; Tiansheng Zhao; Jianyu Wei; Guozong Yue; Xiaojiao Yang (Fuel, 2025)

In situ construction of ion/electron conductive components via lithiation strategy enhancing cycling capability and initial Coulombic efficiency of Si anode - Jingfeng Cao; Xiang Yan; Dan Li; Liuyi Hu; Tiansheng Chen; Weiwei Gao; Wenlong Song; Xinhui Xia; Yang Xia; Wenkui Zhang; Hui Huang (Chemical Engineering Journal, 2025)

Large-scale structural covariance networks changes relate to executive function deficit in betel quid-dependent chewers - Yihao Guo; Tao Liu; Xiaoling Xu; Tiansheng Li; Xiaoli Xiong; Huijuan Chen; Weiyuan Huang; Xianchang Zhang; Feng Chen (Brain Imaging and Behavior, 2024)

Japanese medaka (Oryzias latipes) Nectin4 plays an important role against red spotted grouper nervous necrosis virus infection - Ronggui Dai; Bilin Xia; Mengyang Wang; Mingxi Huang; Lei Chen; Yan Huang; Tiansheng Chen (Fish & Shellfish Immunology, 2024)

Investigation of denitrification to Anammox phase transformation performance of Up-Flow anaerobic sludge blanket reactor - Tiansheng Lu; Qiaoyue Zheng; Angui Huang; Jiannv Chen; Xiangyin Liu; Yujie Qin (Bioresource Technology, 2024)

Photothermal-assisted for ultrafast response acetone sensing with ZIF-90/GO coated microfiber long period gratings - Yan Huang; Wenfu Lin; Ziruo Zhang; Zhenru Li; Tiansheng Huang; Jie Li; Li-Peng Sun; Bai-Ou Guan (Chemical Engineering Journal, 2023)

The rapid start-up of CANON process through adding partial nitration sludge to ANAMMOX system - Siyuan Gong; Yujie Qin; Shaohong Zheng; Tiansheng Lu; Xiangjing Yang; Ming Zeng; Hongen Zhou; Jiannv Chen; Weichan Huang (Journal of Environmental Management, 2023)

miR-24-3p Regulates Epithelial–Mesenchymal Transition and the Malignant Phenotype of Pancreatic Adenocarcinoma by Regulating ASF1B Expression - Wentao Huang; Tiansheng Lin; Long Huang; Junyi Wu; Jiaming Hong; Funan Qiu; Yifeng Tian; Yaodong Wang (Biochemical Genetics, 2023)
Anti-silencing function protein 1 homolog B (ASF1B) has been implicated in the occurrence and development of cancers. The present work explored the functional role and the expression regulation of ASF1B in pancreatic ductal adenocarcinoma (PDAC). Based on the real-time quantitative PCR (qRT-PCR) and immunohistochemistry (IHC), ASF1B was significantly upregulated in PDAC tissues. High expression of ASF1B was associated with a poor overall survival (OS) and recurrence-free survival (DFS) in the PDAC patients. ASF1B also showed a relatively higher expression in PDAC cells (AsPC-1, PANC-1) when compared with human pancreatic ductal epithelial cells (HPDFe-6). CCK8 and clone formation assay demonstrated that silencing ASF1B impaired the proliferation in PANC-1 and AsPC-1 cells, and Annexin V-PI staining showed an increased level of apoptosis upon ASF1B silencing. ASF1B silencing also suppressed the migration and invasion in PDAC cells, as revealed by Transwell assays. We further showed that miR-24-3p was downregulated in PDAC tissues and cells, which functionally interacted with ASF1B by dual-luciferase reporter assay. miR-24-3p negatively regulated ASF1B expression to modulate the malignant phenotype of PDAC cells. ASF1B shows high expression in PDAC, which promotes the malignancy and EMT process of PDAC cells. miR-24-3p is a negative regulator of ASF1B and is downregulated in PDAC cells. Our data suggest that targeting ASF1B/miR-24-3p axis may serve as an intervention strategy for the management of PDAC.

Natural variation of the BRD2 allele affects plant height and grain size in rice - Jinpeng Huang; Zhiming Chen; Jiajia Lin; Jinwen Chen; Menghao Wei; Liang Liu; Feng Yu; Zesen Zhang; Fangyu Chen; Liangrong Jiang; Jingsheng Zheng; Tiansheng Wang; et al. (Planta, 2022)

Human heart cell proteins interacting with a C-terminally truncated 2A protein of coxsackie B3 virus: identification by the yeast two-hybrid system - Tiansheng Zhao; Xiaotian Huang; Yanhua Xia (Virus Genes, 2016)